The lockheed P-38 Lightning - Bodie, Warren M. (Widewing Publication Hiawassee, Georgia, 1991)
The definitive story of the Lockheed's P-38 fighter.
65928
Keywords: Lockheed Aircraft; Military -- Aircrafts; Military aircraft -- History